PERANAN SISTEM PENGENDALIAN INTERNAL DALAM PENANGGULANGAN PIUTANG TAK TERTAGIH - Valentina Christabella Kuncara (AJAR, 2021)
The internal control system, if implemented properly, will certainly create a systematic work procedure and make it in accordance with the rules used in the organization. This research aims to determine and also explain the role of the internal control system in handling uncollectible accounts receivable. This study uses a qualitative descriptive analysis method. This data is processed and obtained through observation, interviews and documentation. The population and sample in this study are social conditions with the sampling technique used is purposive sampling. The interviewees of this research are part of ARH and AR. The results of this study show that the role of the internal control system in overcoming uncollectible accounts receivable when the customer has become a WO is no longer paying the installments, but paying all the arrears. When the debtor is not with the unit, the company will involve a third party, namely PT which is engaged in securing assets.